The NSERC Program of University Research Fellowships - Kavanagh, Robert J. (Canadian Journal of Higher Education, 1987)
In the mid-1970s several analyses warned of an impending crisis in Canadian universities resulting from the age distribution of faculty members and anticipated trends in student enrolments. It was feared that many young Canadians with new doctoral degrees would be unable to enter academic careers and that the universities would suffer from a lack of young research-oriented faculty members. This paper describes the University Research Fellowships program which was introduced by the Natural Sciences and Engineering Research Council in 1980 as a response to this situation. The steps leading up to the launching of the program, the experience with this program to date, and its impact upon the universities are described. Finally, the Council's plans for the future of this program are discussed.